PEMANFAATAN LIMBAH ORGANIK GUNA OPTIMALISASI PRODUKSI KOPI ORGANIK SEBAGAI UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DAN PENGEMBANG DESA AGROWISATA SAMOSIR - Hengki Mangiring Parulian Simarmata; Henry Dunan Pardede; Nancy Florida Siagian; Roy Sahputra Saragih (Politeknik Bisnis Indonesia, 2023)
This research aims to increase the income of village communities in Pangururan District by utilizing organic waste to optimize coffee production and develop the concept of agrotourism villages as one of the tourism supporters in Pangururan District, Samosir Regency. The research method used was descriptive qualitative with a sample size of 28 respondents distributed among 4 farmer groups and carried out by observation and interviews. Based on the research results, the following findings were obtained: (1) The potential for organic waste such as livestock waste, coffee husks, and corn cobs is very large for processed, (2) Farmers who process and utilize agricultural and livestock waste are still 10 percent and the majority use chemical fertilizers, (3) Farmers who have used organic fertilizers on their coffee plants are not optimal and have problems with product marketing, 4. Agrotourism development has not been supported by utilization. existing natural potential. To increase the income of farming communities, a strategy is needed to utilize agricultural and livestock waste as quality organic fertilizer to support increased organic coffee production and the development of agro-tourism destinations.